PENGARUH LIKUIDITAS, MANAJEMEN LABA, KOMISARIS INDEPENDEN DAN KOMPENSASI EKSEKUTIF TERHADAP AGRESIFITAS PAJAK (Studi Empiris pada Perusahaan Perbankan yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2014-2015) - Winda Sri Ayu; Azwir Nasir; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to analyze the influence of liquidity, earnings management, independent commissioners, and executive compensation of tax aggressiveness. The population in the study is a Banking Company Registered in Indonesia Stock Exchange in the period 2014-2015. The sample is taken by using purposive sampling method, where the banking company that issued the financial statements, listed its shares and did not have negative profit during the period 2014-2015. The design in the study is hypothesis testing, where the sample consists of 58 samples. Data processing using multiple linear regression with SPSS 17.0. The results of this study found that liquidity, earnings management and independent komisais affect tax aggressiveness, while executive compensation does not affect the aggressiveness of taxes. Keywords: liquidity, earnings management, independent commissioner, executive compensation, tax aggressiveness